2015
DOI: 10.1109/tgrs.2015.2429917
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Backscatter From Arctic Lake Ice and Polarimetric Implications

Abstract: Polarimetric synthetic aperture radar satellite and ground-based Ku-and X-band scatterometer measurements are used to explore the scattering mechanism for ice in shallow Arctic lakes, wherein strong radiometric responses are seen for floating ice, and low returns are evident where the ice has grounded. Scatterometer measurements confirm that high backscatter is from the ice/water interface, whereas polarimetric decomposition suggests that the dominant scattering mechanism from that interface is single bounce. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 36 publications
7
45
0
1
Order By: Relevance
“…This indicates that the scattering mechanisms causing high σ 0 in the co-polarized image are also sufficient to depolarise incident microwaves. Consistently high backscatter in both the VV and VH observations also indicate that even if grey ice is present at the surface in Husky Lakes, the majority of power returned would be caused by the interaction at or near the ice-water interface [46,47]. Therefore, if surface-ice types and a rough interface caused by tubular bubble development are both present, the σ 0 return from the surface will be of much lower magnitude than surface interaction returns from the ice-water interface.…”
Section: Magic Segmentation-husky Lakesmentioning
confidence: 67%
“…This indicates that the scattering mechanisms causing high σ 0 in the co-polarized image are also sufficient to depolarise incident microwaves. Consistently high backscatter in both the VV and VH observations also indicate that even if grey ice is present at the surface in Husky Lakes, the majority of power returned would be caused by the interaction at or near the ice-water interface [46,47]. Therefore, if surface-ice types and a rough interface caused by tubular bubble development are both present, the σ 0 return from the surface will be of much lower magnitude than surface interaction returns from the ice-water interface.…”
Section: Magic Segmentation-husky Lakesmentioning
confidence: 67%
“…This large dielectric contrast causes a strong reflectance of the radar signal from the ice-water interface. Using polarimetric analysis, recent studies have demonstrated that the single bounce at this interface is the main mechanism of backscattering from the floating ice [36,37]. Thus, backscatter intensity in the case of floating ice is mostly controlled by roughness at the ice-water interface.…”
Section: Ice Groundingmentioning
confidence: 99%
“…These scenes have been acquired in Cband (approximately 5.6 cm wavelength) and HH polarizations. Backscatter intensity varies strongly for floating ice in HH with respect to incidence angle (Atwood et al, 2015). This needs to be considered for large area operational classifications and has not been addressed in previous studies.…”
mentioning
confidence: 99%
“…Duguay et al (2002) find that backscatter intensity from floating ice measured at shallower incidence angles can be similar to that observed from ground-fast ice where only small amounts of bubbles are present. This may relate to a smooth ice water boundary taking into account findings of Atwood et al (2015). Atwood et al (2015) have used a coherent numerical model to test the impact of bubbles upon the lake ice backscatter.…”
mentioning
confidence: 99%
See 1 more Smart Citation